Организация труда комплаенс-службы в структуре управления предприятием - Кобелева, Татьяна Александровна (Белорусский национальный технический университет, 2018)
В статье рассмотрены вопросы формирования служб комплаенс на промышленных предприятиях. Обобщен опыт использования комплаенс функции, который показывает, что там, где система комплаенс является неотъемлемой частью корпоративного управления, возникают реальные предпосылки к росту конкурентоспособности предприятия и его продукции. Доказано, что содержание программы деятельности службы комплаенс должно определяться в соответствии с конкретными требованиями промышленного предприятия. Определено ее место в структуре управления предприятий, использующих комплаенс службу, разработана система взаимодействия службы комплаенс с производственными и управленческими подразделениями. Такое взаимодействие позволяет своевременное выявление комплаенс рисков и их уменьшение или полное устранение. Предложена структура должностей комплаенс службы и определены их должностные функции.

The article deals with the formation of compliance services in industrial enterprises. Summarizes the experience of using the compliance function, which shows that where the compliance system is an integral part of corporate governance, there are real prerequisites for an increase in the competitiveness of an enterprise and its products. It is proved that the content of the program of activities of the compliance service should be determined in accordance with the specific requirements of the industrial enterprise. Its place in the management structure of enterprises using the compliance service has been determined; a system of interaction of the compliance service with production and management units has been developed. Such interaction allows timely detection of compliance risks and their reduction or complete elimination. The structure of posts of service compliance was proposed and their official functions were determined.
Organization of labor of compliance services in the structure of management of the enterprise
Keywords: предприятие промышленное; обязанности должностные; менеджер; контроль; industrial enterprises; official duties; manager; control